On the adaptive synchronous control of a large-scale dual-shaker platform system - Li, Xinhui (2022)
There is an ever-increasing requirement for higher power vibrating platforms to test large-scale structures. Whilst this may be achieved with a single shaker, this is an expensive option. An alternative solution is to drive a platform with two or more smaller shakers. To do this effectively, however, requires the identical amplitude and phase response of the shakers. In practice, due to manufacturing tolerances and uneven loading, this is not possible without a control system. The design and implementation of such a system is the objective of this paper. An adaptive FxLMS algorithm is used in the synchronous control of a dual-shaker system, considering the dynamic coupling between the shakers. A simulation is presented to verify the effectiveness of the control algorithm before the control system is integrated with practical a dual-shaker system driving a vibrating platform. It is shown that there are significant differences between the controlled and the uncontrolled system, demonstrating the efficacy of the control approach.